Glucose-derived AGEs promote migration and invasion of colorectal cancer by up-regulating Sp1 expression - Deng, Ruyuan; Wu, Huo; Ran, Hui; Kong, Xiang; Hu, Lei; Wang, Xiao; Su, Qing (Biochimica et biophysica acta. General subjects, 2017)
It is well established that the risk of colorectal cancer (CRC) is significantly increased in diabetic patients. As one of main forms of the advanced glycation end products (AGEs) that accumulate in vivo, glucose-derived AGEs play an important role in the pathogenesis of diabetic complications and may contribute to CRC progression. However, to date, both the contribution of glucose-derived AGEs to the course of CRC and the underlying mechanism are unclear. In the present study, the concentration of glucose-derived AGEs in the serum and tumor tissue of patients with CRC increased. A clinical data analysis demonstrated that the expression of the receptor for AGEs (RAGE), Specificity Protein 1 (Sp1), and matrix metallopeptidase −2 (MMP2) was significantly higher in cancerous tissues compared with non-tumor tissue in Chinese Han patients with CRC and that RAGE expression was closely associated with lymph node metastasis and TNM stage. Furthermore, in vivo and in vitro experiments showed that AGEs promoted invasion and migration of colorectal cancer, and the AGEs treatment increased the expression of RAGE, Sp1, and MMP2 in a dose-dependent manner. A RAGE blocking antibody and an Sp1-specific siRNA attenuated the AGE-induced effects. Moreover, the AGEs treatment increased the phosphorylation of ERK, and reducing the phosphorylation level of ERK by MEK1/2 inhibitor decreased the expression of Sp1. In conclusion, glucose-derived AGEs promote the invasion and metastasis of CRC partially through the RAGE/ERK/SP1/MMP2 cascade. These findings may provide an explanation for the poor prognoses of colorectal cancer in diabetic patients. •Accumulation of glucose-AGEs in sera and expression of RAGE, Sp1, and MMP2 in tumor tissue of CRC patients were increased.•High expression of RAGE in cancer tissues is positively associated with the metastasis of colorectal cancer.•AGEs promote colorectal liver metastasis in vivo and in vitro and stimulate RAGE, Sp1, and MMP2 expression in CRC cells.•Sp1 mediates the AGE-induced migration and invasion of colorectal cancer cells and the AGEs/RAGE/ERK/MMP2 cascade.